Experimental Infection of Ticks: An Essential Tool for the Analysis of Babesia Species Biology and Transmission - Sarah I. Bonnet (MDPI AG, 2021)
Babesiosis is one of the most important tick-borne diseases in veterinary health, impacting mainly cattle, equidae, and canidae, and limiting the development of livestock industries worldwide. In humans, babesiosis is considered to be an emerging disease mostly due to Babesia divergens in Europe and Babesia microti in America. Despite this importance, our knowledge of Babesia sp. transmission by ticks is incomplete. The complexity of vectorial systems involving the vector, vertebrate host, and pathogen, as well as the complex feeding biology of ticks, may be part of the reason for the existing gaps in our knowledge. Indeed, this complexity renders the implementation of experimental systems that are as close as possible to natural conditions and allowing the study of tick-host-parasite interactions, quite difficult. However, it is unlikely that the development of more effective and sustainable control measures against babesiosis will emerge unless significant progress can be made in understanding this tripartite relationship. The various methods used to date to achieve tick transmission of Babesia spp. of medical and veterinary importance under experimental conditions are reviewed and discussed here.